Advanced management for deans - Friel, Terri (Emerald Publishing Limited : Information Age Pub. Inc., 2016)
Deanships in the world are often OTJ (On the job training) positions. Prior to this series, there was very little about this specific position and how to be innovative and successful on the job. This book is the second in the series of Management for Deans and includes advanced techniques employed by deans around the world to manage their boards, planning, donors, and careers. If you've been a dean or are considering this position, the series Management for Deans and Advanced Management for Deans will introduce you to the position and offer you many ideas from experienced deans around the world that can accelerate your success and help you avoid the pitfalls of OTJ.